2014
DOI: 10.1111/ajco.12172
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of neoadjuvant concurrent chemoradiotherapy versus up-front proctectomy in clinical stage II-III rectal cancer: A population-based study

Abstract: We demonstrated that the use of neoadjuvant concurrent systemic therapy and radiotherapy is associated with better effectiveness in rectal adenocarcinoma of clinical stage II-III as compared with up-front proctectomy. Further studies are needed to elucidate the subgroups most likely to benefit and to clarify NCCRT's cost-effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…[9] Compared with upfront surgery, the possible advantages of neoadjuvant CRT in the treatment of LARC include gained resectability and an increased rate of sphincter preservation. [7,10] According to the results of the German CAO/ARO/AIO-94 randomized phase III trial, preoperative CRT showed improved pelvic control and sphincter preservation and less acute/chronic toxicity than postoperative chemoradiotherapy, [7] and there is a persisting significant improvement of pre versus postoperative CRT on local control. [7,8] There is also evidence that showed that preoperative CRT reduce overall long-term surgical complications compared with postoperative CRT.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Compared with upfront surgery, the possible advantages of neoadjuvant CRT in the treatment of LARC include gained resectability and an increased rate of sphincter preservation. [7,10] According to the results of the German CAO/ARO/AIO-94 randomized phase III trial, preoperative CRT showed improved pelvic control and sphincter preservation and less acute/chronic toxicity than postoperative chemoradiotherapy, [7] and there is a persisting significant improvement of pre versus postoperative CRT on local control. [7,8] There is also evidence that showed that preoperative CRT reduce overall long-term surgical complications compared with postoperative CRT.…”
Section: Introductionmentioning
confidence: 99%
“…We then used the logit of the probability as the PS, as is typically used in the literature (14). We defined the co-variables based on our prior clinical-and HWDC-related research experiences (15)(16)(17). We Statistical and supplementary analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Secondly, we collected additional factors that might affect both the use and cost of NCCRT for locally advanced esophageal cancer patients based on our clinical and research experiences. In this regard, we also included patient demographic factors (age, gender, and residency), patient characteristics (comorbidity, SES), disease (stage), and health service provider characteristics (treating hospital level and surgeon's experience) based on our clinical experiences and prior NHI Research Database (NHIRD) and HWDC related studies . Patient residency was classified as northern Taiwan or non‐north; hospital was classified as medical centers or regional hospitals.…”
Section: Methodsmentioning
confidence: 99%